Magnetic resonance visual hydrogel material capable of dynamically monitoring tissue reconstruction as well as preparation method and application of magnetic resonance visual hydrogel material

By embedding trivalent gadolinium ions into the matrix of sodium alginate and ammonium alginate and combining with crosslinking compositions, the imaging efficiency and mechanical properties of magnetic resonance hydrogel materials are improved, and the imaging efficiency in the prior art is solved. The problems of poor mechanical properties and poor stability have achieved real-time monitoring of the tissue repair process and improved biosafety.

CN119113210APending Publication Date: 2024-12-13RUIJIN HOSPITAL AFFILIATED TO SHANGHAI JIAO TONG UNIV SCHOOL OF MEDICINE
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411047521.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-01
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing magnetic resonance hydrogel materials have low imaging efficiency, poor mechanical properties and poor stability, and cannot effectively monitor the tissue repair process. The commonly used gadolinium ion contrast agents have problems such as risk of toxicity and high background noise.

Method used

Embed trivalent gadolinium ions into the matrix of sodium alginate and ammonium alginate to form stable nanoparticles or complexes and are enhanced by crosslinking compositions such as carboxy modified polyvinyl alcohol, thiolated hyaluronic acid and chitosan The mechanical properties and stability of hydrogels extend the imaging window and service life.

Benefits of technology

It improves the contrast and resolution of magnetic resonance imaging, extends the service life and storage time of hydrogels, realizes real-time non-invasive monitoring of hydrogel scaffold materials and accurate positioning and tracking of tissue regeneration processes, and enhances biosafety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004973907180000021
    Figure BDA0004973907180000021
  • Figure FDA0004973907160000011
    Figure FDA0004973907160000011
Patent Text Reader

Abstract

The invention discloses a magnetic resonance visual hydrogel material capable of dynamically monitoring tissue reconstruction, and belongs to the technical field of tissue repair materials. The material comprises a modified gadolinium contrast agent, a cross-linking composition, methacrylic anhydride gelatin, a cross-linking agent and a photoinitiator, the modified gadolinium contrast agent comprises sodium alginate, ammonium alginate and trivalent gadolinium ions, and the cross-linking composition comprises carboxyl modified polyvinyl alcohol, sulfhydrylated hyaluronic acid and chitosan. According to the invention, trivalent gadolinium ions are embedded into a matrix of sodium alginate and ammonium alginate to form stable nanoparticles or a compound, so that the sensitivity is improved, an imaging window is prolonged, the degradation process of a stent material can be continuously tracked, and the mechanical property and the stability of the hydrogel are improved through a cross-linking composition; the service life and the preservation time of the hydrogel are prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of tissue repair materials, and in particular relates to a magnetic resonance visualization hydrogel material capable of dynamically monitoring tissue reconstruction, a preparation method and an application thereof. Background Art

[0002] Hydrogel materials are a promising scaffold material for tissue repair due to their good biocompatibility and adjustable tissue microenvironment adaptability. However, in order to achieve the ideal tissue repair effect, the hydrogel scaffold needs to have a degradation rate that is compatible with the regeneration process of new tissue. In order to obtain a sustained and stable repair effect and realize clinical application transformation in the future, it is necessary to understand what happens after the material is implanted in the body, and an effective and feasible method is to achieve real-time non-invasive monitoring.

[0003] Currently, hydrogel materials have been tracked through fluorescent labeling, near-infrared imaging, carbon nanodot modification, or 19F radionuclide imaging. However, fluorescence monitoring usually results in diffuse signals, which cannot accurately reflect the degradation process and exact anatomical location of the implant, and whether the degradation process matches the regeneration process. However, matching the degradation rate of the hydrogel material with the rate of tissue regeneration is the key point in determining whether the repair can be successful in the end. Therefore, it is necessary to design a hydrogel material that can be directly imaged, which can not only accurately locate, but also continuously and in situ track the degradation process of the hydrogel scaffold while non-invasively monitoring tissue regeneration.

[0004] Magnetic resonance imaging (MRI) has a variety of imaging sequences with good spatial resolution and high sensitivity to soft tissues, which can provide effective feedback for the real-time status of in situ hydrogel materials. In order to improve diagnostic accuracy, contrast agents are often used to enhance the image signal-to-noise ratio. Commonly used MRI contrast agents are low-molecular chelates based on gadolinium (Gd) ions, which have small molecular weight, low tissue specificity, and high metabolic rate. However, they have the disadvantages of high background noise and too narrow imaging time window. Low relaxivity also increases the dosage of contrast agents, increasing the risk of long-term toxic reactions, such as chronic kidney disease.

[0005] In order to solve the problem of low relaxivity of gadolinium ions, magnetic resonance contrast agents are often combined with macromolecular chains, which have the advantages of high imaging efficiency and low toxicity, and can realize in vivo, real-time, and in-situ monitoring of stent materials through MRI. However, most of the existing studies introduce small molecule contrast agents into the biomaterial system by physical blending. The contrast agent does not form a molecular chain with the stent material, resulting in no significant improvement in its T1 relaxation rate. In addition, there are problems of low mechanical strength and low stability, which shortens the storage time of the biomaterial hydrogel. Therefore, there is an urgent need for a hydrogel material with high imaging efficiency, high mechanical strength and high stability. Summary of the invention

[0006] The purpose of the present invention is to provide a magnetic resonance visualization hydrogel material that can dynamically monitor tissue reconstruction, so as to solve the problems of low imaging efficiency, poor mechanical properties and poor stability of the above-mentioned magnetic resonance hydrogel materials. The present invention embeds trivalent gadolinium ions into the matrix of sodium alginate and ammonium alginate to form stable nanoparticles or complexes, which not only improves sensitivity and extends the imaging window, but also can continuously track the degradation process of the stent material. The mechanical properties and stability of the hydrogel are also improved through the cross-linked composition, extending the service life and storage time of the hydrogel.

[0007] To achieve the above objectives, the first aspect of the present invention provides a magnetic resonance visualization hydrogel material that can dynamically monitor tissue reconstruction. The magnetic resonance visualization hydrogel material includes a modified gadolinium contrast agent, a cross-linking composition, methacrylated gelatin, a cross-linking agent, and a photoinitiator.

[0008] Preferably, the magnetic resonance visualization hydrogel material comprises, by weight percentage:

[0009]

[0010] Preferably, the modified gadolinium contrast agent comprises sodium alginate, ammonium alginate and trivalent gadolinium ions, wherein the molar ratio of sodium alginate: ammonium alginate: trivalent gadolinium ions is (0.5-0.8): (0.1-0.3):6.

[0011] Preferably, the preparation method of the modified gadolinium contrast agent is: dissolving sodium alginate and ammonium alginate in water to obtain an alginate aqueous solution; mixing the alginate aqueous solution with an n-pentylamine aqueous solution and stirring evenly; adding hydrochloric acid to the stirred solution to adjust the pH value to 3-5; then dripping an aqueous solution of trivalent gadolinium ions under stirring; after the dripping of the aqueous solution of trivalent gadolinium ions is completed, adding ethanol, filtering to obtain a precipitate, and drying the precipitate to obtain a modified gadolinium contrast agent.

[0012] At present, the degradation rate and angiogenesis-promoting ability of hydrogels are mainly evaluated by magnetic resonance imaging, but the contrast agent used is directly physically mixed with the stent material, and the mixing effect is poor, which affects the imaging effect. In the present invention, sodium alginate and ammonium alginate are mixed with trivalent gadolinium ions at the same time, wherein both sodium alginate and ammonium alginate are polysaccharides extracted from natural trehalose, and have good biocompatibility and low toxicity. Trivalent gadolinium ions are the most commonly used paramagnetic particles, but free gadolinium ions are toxic and need coordination and encapsulation. In the present invention, gadolinium ions can be embedded in the matrix of sodium alginate and ammonium alginate to form stable nanoparticles or complexes. These structures can be more effectively enriched in the corresponding area, enhance local MRI signals, and improve image contrast and resolution.

[0013] The inventors also found that, in the system of the present invention, the use of sodium alginate and ammonium alginate in a specific ratio can not only enhance image contrast and resolution, but also increase the stability of the hydrogel, because different alginates have different physical and chemical properties and different adaptability. In the present invention, once the addition ratio of ammonium alginate is increased, the stability will decrease.

[0014] Preferably, the preparation method of methacrylic anhydride gelatin is: dissolving gelatin in deionized water and stirring to obtain a gelatin solution; then adding methacrylic anhydride dropwise to the gelatin solution; dialyzing and freeze-drying the mixed solution after the addition to obtain methacrylic anhydride gelatin;

[0015] The mass volume ratio of gelatin and methacrylic anhydride is 1g:0.1-0.2mL.

[0016] Preferably, the cross-linked composition comprises carboxyl-modified polyvinyl alcohol, thiolated hyaluronic acid and chitosan;

[0017] The mass ratio of carboxyl-modified polyvinyl alcohol: thiolated hyaluronic acid: chitosan is (5-10): (0.5-1): (2-4);

[0018] The deacetylation degree of chitosan is ≥95%, the viscosity is 100-200 mPa·s, and the molecular weight is 200,000-260,000.

[0019] Preferably, the preparation method of carboxyl-modified polyvinyl alcohol is:

[0020] Add 3-6 g of polyvinyl alcohol into 200 mL of water, completely dissolve at 85-90° C., and cool to room temperature to obtain a polyvinyl alcohol solution;

[0021] 100 mL of 2M sodium hydroxide solution and 5-8 g of acrylonitrile were mixed evenly, and then added dropwise to the polyvinyl alcohol solution to carry out addition reaction at 0°C. After the reaction was completed, the mixture was filtered, and the filtrate was extracted with dichloromethane. The extracted dichloromethane solution was rotary evaporated to obtain the intermediate product, cyano-modified polyvinyl alcohol;

[0022] The cyano-modified polyvinyl alcohol was dissolved in 100 mL of methanol, and then added into a mixed solution of 120 mL of NaOH and methanol, and hydrolyzed at 30-50° C. for 1-3 hours. The pH was adjusted to neutral, and deionized water was added dropwise to obtain a gel product, which was washed and dried to obtain carboxyl-modified polyvinyl alcohol.

[0023] Preferably, the preparation process of carboxyl-modified polyvinyl alcohol is:

[0024] Add 4.4 g of polyvinyl alcohol into 200 mL of water, completely dissolve at 90°C, and cool to room temperature to obtain a polyvinyl alcohol solution;

[0025] 100 mL of 2M sodium hydroxide solution and 6.4 g of acrylonitrile were mixed evenly, and then added dropwise to the polyvinyl alcohol solution to carry out addition reaction at 0°C. After the reaction was completed, the mixture was filtered, extracted with dichloromethane, and rotary evaporated to obtain the intermediate product, cyano-modified polyvinyl alcohol;

[0026] Dissolve cyano-modified polyvinyl alcohol in 100 mL of methanol, add 120 mL of a mixed solution of NaOH and methanol, the ratio of NaOH to methanol being 40 g:1 L, carry out a hydrolysis reaction at 40°C for 2 h, adjust the pH to neutral, drop deionized water as a precipitant to obtain a gel-like product, wash, and dry to obtain carboxyl-modified polyvinyl alcohol.

[0027] Preferably, the thiolated hyaluronic acid is one of hyaluronic acid-cysteine, hyaluronic acid-cysteamine, hyaluronic acid-cysteine ​​methyl ester, hyaluronic acid-cysteine ​​ethyl ester, or a mixture thereof.

[0028] Preferably, the thiolated hyaluronic acid has hyaluronic acid as the skeleton, and the amino group of the amino acid substance is covalently bonded with the carboxyl group of the hyaluronic acid to form an amide bond. The amino acid substance includes one of cysteine ​​hydrochloride, cysteamine hydrochloride, cysteine ​​methyl ester hydrochloride, and cysteine ​​ethyl ester hydrochloride.

[0029] Taking the preparation of hyaluronic acid-cysteine ​​as an example, the specific preparation process is as follows: 200 mg of 5×10 5 Da of sodium hyaluronate was dissolved in 50 ml of deionized water to obtain a 0.4% hyaluronic acid solution, and 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride (EDAC) and 0.58% N-hydroxysuccinimide (NHS) were added to the final concentration of 0.96%, and the pH was adjusted to 5.5 after dissolution, and stirred for 45 minutes; 400 mg of cysteine ​​hydrochloride was added, and the pH of the reaction solution was adjusted to 4.75, and the reaction was protected from light for 5 hours. After the reaction was completed, the reaction mixture was placed in a dialysis bag with a molecular weight cutoff of 3500Da, and dialyzed with HCl solution (pH4), HCl solution containing 1% NaCl (pH4), and HCl solution (pH4) in turn, and freeze-dried to obtain hyaluronic acid-cysteine.

[0030] The prior art often uses a single component as a cross-linking material in the process of preparing hydrogels, but a single component has limitations in mechanical properties, such as low strength and poor toughness, which limits its application in tissue engineering scaffolds and wound dressings. It also has the problem of poor stability and is easily degraded. Its performance degrades during long-term storage, affecting its service life. The cross-linking composition in the present invention includes three substances: carboxyl-modified polyvinyl alcohol, thiolated hyaluronic acid and chitosan, wherein carboxyl-modified polyvinyl alcohol can provide additional cross-linking points by introducing carboxyl functional groups, especially in the cross-linking process induced by using multivalent metal ions or by external conditions such as light and heat. These cross-linking points can enhance the physical or chemical stability of the hydrogel network, thereby improving the overall mechanical strength and durability; the thiol group in the thiolated hyaluronic acid has a strong hydrogen bond forming ability and a reversible disulfide bond forming potential, so that the thiolated hyaluronic acid can form disulfide bonds after injury. Bond exchange reactions achieve self-repair, which is crucial for applications that require long-term stability and damage recovery. This dynamic cross-linking property increases the toughness of the hydrogel and allows it to restore its structure when subjected to external pressure or damage. Chitosan is a natural polysaccharide with a positive charge that can form electrostatic attraction with negative charges (such as carboxyl or sulfate groups) in thiolated hyaluronic acid, as well as ionic interactions with carboxyl groups in carboxyl-modified polyvinyl alcohol. These interactions enhance the compatibility and interfacial adhesion between different components, and help to construct a more uniform composite hydrogel with stronger mechanical properties.

[0031] During the research and development of the present invention, it is found that in the system of the present invention, although the mechanical properties of the hydrogel are improved by designing the type of the cross-linked composition, its stability is insufficient and the service life is short. For the above problems, the present invention further adjusts the ratio of three substances of carboxyl-modified polyvinyl alcohol, thiolated hyaluronic acid and chitosan. Under the ratio limited by the present invention, the three substances have multiple cross-linking mechanisms, and a stable network structure can be formed by cross-linking between carboxyl-modified polyvinyl alcohol and chitosan. At the same time, the sulfhydryl group in the thiolated hyaluronic acid can form a reversible disulfide cross-linking under certain conditions. This multiple cross-linking mechanism significantly enhances the physical stability and chemical stability of the hydrogel, making it more resistant to external environmental changes (such as temperature, pH fluctuations) and mechanical stress. The interaction between chitosan and carboxyl-modified polyvinyl alcohol and thiolated hyaluronic acid in the present invention can optimize the phase interface inside the material, reduce the phase separation phenomenon, and enhance the consistency and stability of the entire hydrogel system.

[0032] Preferably, the crosslinking agent is one of N,N'-methylene acrylamide, ethylene glycol dimethacrylate, divinylbenzene, hydroxyalkyl methacrylate or a mixture thereof.

[0033] Preferably, the photoinitiator is one of 1-hydroxycyclohexyl phenyl ketone, diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide, phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, or a mixture thereof.

[0034] The second aspect of the present invention provides a method for preparing the aforementioned magnetic resonance visualization hydrogel material capable of dynamically monitoring tissue reconstruction, comprising the following steps:

[0035] a) mixing the modified gadolinium contrast agent, the cross-linking composition, and methacrylic anhydride gelatin in water to obtain a mixed solution A;

[0036] b) adding a cross-linking agent to the mixed solution A under stirring to obtain a mixed solution B;

[0037] c) adding a photoinitiator to the mixed solution B to obtain a mixed solution C;

[0038] d) Mixed solution C is subjected to polymerization reaction under ultraviolet light, and after the reaction is completed, a mixture D is obtained;

[0039] e) The mixture D is centrifuged to obtain a solid, and the obtained solid is washed and dried to obtain a magnetic resonance visualized hydrogel material that can dynamically monitor tissue reconstruction.

[0040] A third aspect of the present invention provides an application of a magnetic resonance visualized hydrogel material capable of dynamically monitoring tissue reconstruction in the preparation of a tissue repair material.

[0041] Therefore, the present invention uses the above-mentioned magnetic resonance visualization hydrogel material that can dynamically monitor tissue reconstruction, which has the following beneficial effects:

[0042] 1. In the present invention, trivalent gadolinium ions are embedded into the matrix of sodium alginate and ammonium alginate to form stable nanoparticles or complexes, which can aggregate in the measurement area, enhance the local MRI signal, and improve the contrast ratio and resolution of the image. The modified gadolinium contrast agent of the present invention not only improves the sensitivity and extends the imaging window, but also can continuously track the degradation process of the stent material, and can realize the real-time non-invasive monitoring of the state of the biomaterial in vivo in vitro.

[0043] 2. The cross-linked composition of the present invention includes carboxyl-modified polyvinyl alcohol, thiolated hyaluronic acid and chitosan. During the polymerization process, the three act synergistically to improve the stability and mechanical properties of the hydrogel and extend the service life of the hydrogel.

[0044] 3. The present invention can achieve accurate positioning of tracking through the production of the hydrogel material, and can continuously and in situ track the degradation process of the hydrogel scaffold, while non-invasively monitoring tissue regeneration, and adopts magnetic resonance imaging technology, which has a variety of imaging sequences, good spatial resolution and high sensitivity to soft tissue, and can provide effective feedback for the real-time status of the in situ hydrogel material. By designing a contrast agent-integrated hydrogel scaffold for tissue repair, it can not only improve the sensitivity and biosafety, extend the imaging window, but also continuously track the degradation process of the scaffold material, thereby realizing real-time non-invasive monitoring of the in vivo status of the biomaterial in vitro.

[0045] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION

[0046] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.

[0047] Example 1

[0048] This embodiment provides a magnetic resonance visualization hydrogel material capable of dynamically monitoring tissue reconstruction, which comprises, by mass percentage, 0.3% of a modified gadolinium contrast agent, 58.5% of a cross-linking composition, 25% of methacrylic anhydride gelatin, 15% of a cross-linking agent, and 1.2% of a photoinitiator;

[0049] The modified gadolinium contrast agent includes sodium alginate, ammonium alginate and trivalent gadolinium ions, and the molar ratio of sodium alginate, ammonium alginate and trivalent gadolinium ions is 0.5:0.2:6;

[0050] The cross-linked composition comprises carboxyl-modified polyvinyl alcohol, thiolated hyaluronic acid and chitosan, and the mass ratio of the carboxyl-modified polyvinyl alcohol, thiolated hyaluronic acid and chitosan is 5:0.5:3.

[0051] The preparation process of the modified gadolinium contrast agent is as follows: at 20° C., a mixed aqueous solution of sodium alginate and ammonium alginate is mixed with an aqueous solution of n-pentylamine, wherein the mass percentage concentration of n-pentylamine in the aqueous solution of n-pentylamine is 3%, the total mass percentage concentration of sodium alginate and ammonium alginate in the mixed aqueous solution of sodium alginate and ammonium alginate is 1%, and the molar ratio of sodium alginate to n-pentylamine is 1:0.3; the mixing is accompanied by stirring, the pH value of the system is adjusted to 4 with a 0.1 mol / L HCl solution, and then 0.1 mol / L HCl is added dropwise to the mixed solution. .1M trivalent gadolinium ion aqueous solution, the trivalent gadolinium ion aqueous solution in this embodiment adopts gadolinium chloride aqueous solution, stirring after the dropwise addition is completed, the duration is 1 hour, and the hybrid material aqueous solution loaded with gadolinium ions is obtained, and ethanol is added while stirring continuously. Ethanol is used as a precipitant, and the volume ratio of ethanol to the hybrid material aqueous solution is 2:1. The precipitate is collected by suction filtration, and the precipitate is repeatedly rinsed with ethanol twice. The precipitate is dried in a vacuum oven at a temperature of 25°C and a vacuum degree of 0.09 MPa to obtain a modified gadolinium contrast agent.

[0052] The preparation process of methacrylic anhydride gelatin is as follows: 1g gelatin is dissolved in 100mL deionized water to obtain a uniform solution, and then 0.1mL methacrylic anhydride is dropped into it, dialyzed, with a molecular weight cutoff of 10kDa, and freeze-dried to obtain methacrylic anhydride gelatin; the mass volume ratio of gelatin and methacrylic anhydride is 1g:0.1mL.

[0053] Chitosan with a deacetylation degree of ≥95%, a viscosity of 150 mPa·s, and a molecular weight of 250,000 was purchased from Chengdu Zhongjinlong Technology Development Co., Ltd.

[0054] The preparation process of carboxyl-modified polyvinyl alcohol is as follows:

[0055] 4.4 g of polyvinyl alcohol was added to 200 mL of water, completely dissolved at 90° C., and cooled to room temperature to obtain a polyvinyl alcohol solution; polyvinyl alcohol was purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.;

[0056] 100 mL of 2M sodium hydroxide solution and 6.4 g of acrylonitrile were mixed evenly, and then added dropwise to the polyvinyl alcohol solution. The mixture was reacted at 0°C for 5 h. After the reaction was completed, the mixture was filtered, extracted with dichloromethane, and rotary evaporated to obtain the intermediate product, cyano-modified polyvinyl alcohol.

[0057] Dissolve cyano-modified polyvinyl alcohol in 100 mL of methanol, add 120 mL of a mixed solution of NaOH and methanol, the ratio of NaOH to methanol being 40 g:1 L, carry out a hydrolysis reaction at 40°C for 2 h, adjust the pH to neutral, drop deionized water as a precipitant to obtain a gel-like product, wash, and dry to obtain carboxyl-modified polyvinyl alcohol.

[0058] The thiolated hyaluronic acid is hyaluronic acid-cysteine.

[0059] The specific preparation process of hyaluronic acid-cysteine ​​is as follows: 200 mg of 5×10 5 Da of sodium hyaluronate was dissolved in 50 ml of deionized water to obtain a 0.4% hyaluronic acid solution, and 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride (EDAC) and 0.58% N-hydroxysuccinimide (NHS) were added to the final concentration of 0.96%, and the pH was adjusted to 5.5 after dissolution, and stirred for 45 minutes; 400 mg of cysteine ​​hydrochloride was added, and the pH of the reaction solution was adjusted to 4.75, and the reaction was protected from light for 5 hours. After the reaction was completed, the reaction mixture was placed in a dialysis bag with a molecular weight cutoff of 3500Da, and dialyzed with HCl solution (pH4), HCl solution containing 1% NaCl (pH4), and HCl solution (pH4) in turn, and freeze-dried to obtain hyaluronic acid-cysteine.

[0060] The cross-linking agent selected was N,N'-methylene acrylamide.

[0061] The photoinitiator selected was diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide, CAS No. 75980-60-8.

[0062] In this embodiment, the above-mentioned components are prepared and selected to prepare the magnetic resonance visualization hydrogel material capable of dynamically monitoring tissue reconstruction of the present application. The specific preparation process includes the following steps:

[0063] a) mixing the modified gadolinium contrast agent, the cross-linking composition, and methacrylic anhydride gelatin in water to obtain a mixed solution A;

[0064] b) adding a cross-linking agent to the mixed solution A under stirring to obtain a mixed solution B;

[0065] c) adding a photoinitiator to the mixed solution B to obtain a mixed solution C;

[0066] d) Mixed solution C is subjected to polymerization reaction under ultraviolet light, and after the reaction is completed, a mixture D is obtained;

[0067] e) The mixture D is centrifuged to obtain a solid, and the obtained solid is washed and dried to obtain a magnetic resonance visualized hydrogel material that can dynamically monitor tissue reconstruction.

[0068] Example 2

[0069] The difference from Example 1 is:

[0070] The magnetic resonance visualization hydrogel material includes, by weight percentage, 0.2% of a modified gadolinium contrast agent, 64% of a cross-linking composition, 15% of methacrylic anhydride gelatin, 20% of a cross-linking agent, and 0.8% of a photoinitiator;

[0071] The modified gadolinium contrast agent includes sodium alginate, ammonium alginate and trivalent gadolinium ions, and the molar ratio of sodium alginate, ammonium alginate and trivalent gadolinium ions is 0.8:0.3:6;

[0072] The cross-linked composition comprises carboxyl-modified polyvinyl alcohol, thiolated hyaluronic acid and chitosan, and the mass ratio of carboxyl-modified polyvinyl alcohol, thiolated hyaluronic acid and chitosan is 8:0.7:4.

[0073] Comparative Example 1

[0074] The difference between this comparative example and Example 1 is that the molar ratio of sodium alginate, ammonium alginate and trivalent gadolinium ion is 0.5:1.5:6, that is, the amount of ammonium alginate used is increased.

[0075] Comparative Example 2

[0076] The difference between this comparative example and Example 1 is that the cross-linked composition includes carboxyl-modified polyvinyl alcohol, thiolated hyaluronic acid and chitosan, and the mass ratio of carboxyl-modified polyvinyl alcohol:thiolated hyaluronic acid:chitosan is 20:0.5:3, that is, the amount of carboxyl-modified polyvinyl alcohol is increased.

[0077] Comparative Example 3

[0078] The difference between this comparative example and Example 1 is that ammonium alginate is not added to the modified gadolinium contrast agent, and an equal amount of sodium alginate is used to replace ammonium alginate.

[0079] Comparative Example 4

[0080] The difference between this comparative example and Example 1 is that the carboxyl-modified polyvinyl alcohol in the cross-linking composition is replaced by an equal amount of polyvinyl alcohol.

[0081] Comparative Example 5

[0082] The difference between this comparative example and Example 1 is that the thiolated hyaluronic acid in the cross-linked composition is replaced by an equal amount of hyaluronic acid.

[0083] Comparative Example 6

[0084] The difference between this comparative example and Example 1 is that the mass volume ratio of gelatin to methacrylic anhydride is 1 g:1 mL, that is, the amount of methacrylic anhydride is increased.

[0085] Comparative Example 7

[0086] The difference between this comparative example and Example 1 is that the viscosity of chitosan is 400 mPa·s, which is purchased from Wuhan Zhuokang New Materials Co., Ltd.

[0087] Performance Testing

[0088] (1) In vitro nuclear magnetic resonance imaging effect The in vitro relaxation efficiency of Examples 1 to 2 and Comparative Examples 1 to 7 was measured and obtained. The test results are shown in Table 1.

[0089] Table 1 In vitro relaxation efficiency test results

[0090] <![CDATA[In vitro relaxation efficacy / mM -1 s -1 > Example 1 318 Example 2 307 Comparative Example 1 235 Comparative Example 2 274 Comparative Example 3 202 Comparative Example 4 261 Comparative Example 5 265 Comparative Example 6 276 Comparative Example 7 253

[0091] From the above performance test results, it can be seen that the in vitro relaxation efficiency of Examples 1-2 is relatively high, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly because the gadolinium ions in Example 1 can be embedded in the matrix of sodium alginate and ammonium alginate to form stable nanoparticles or complexes. These structures can be more effectively enriched in the corresponding area, enhance local MRI signals, and improve image contrast and resolution. At the same time, after the cross-linked composition and other substances undergo polymerization reaction, they can also form good compatibility with the matrix formed by sodium alginate and ammonium alginate, and the gadolinium ions remain stable.

[0092] However, since the necessary technical solutions were not adopted in the comparative examples, the corresponding performance tests were significantly worse than those of the embodiments. In comparative example 1, the proportion of alginate amine in the modified gadolinium contrast agent was changed, and it can be seen that the in vitro relaxation efficiency decreased, proving that the proportion of sodium alginate, ammonium alginate and gadolinium ions in the modified gadolinium contrast agent has an important influence on improving the in vitro relaxation efficiency. In comparative example 2, the proportion of the cross-linked composition was not changed, and in comparative example 3, alginate amine was not added. In comparative example 4, polyvinyl alcohol was used, and in comparative example 5, hyaluronic acid was used. In comparative example 6, the addition ratio of methacrylic anhydride in methacrylic anhydride gelatin was changed, and in comparative example 7, the annual viscosity of chitosan was changed. It can be seen from the results in Table 1 that changing the proportion of raw materials and the type of raw materials will affect the in vitro relaxation efficiency of the hydrogel. The above experimental results further prove the importance of the technical solutions defined in the present invention for its technical effects.

[0093] (2) Mechanical properties test

[0094] The tensile properties test method is as follows: all hydrogel samples were cut into 1.5×5 cm rectangles for uniaxial tensile testing, with a test gauge length of 20 mm and a tensile speed of 100 mm / min. The test results are shown in Table 2.

[0095] Table 2 Mechanical properties test results

[0096] Tensile strength / MPa Example 1 0.519 Example 2 0.502 Comparative Example 1 0.415 Comparative Example 2 0.266 Comparative Example 3 0.407 Comparative Example 4 0.218 Comparative Example 5 0.235 Comparative Example 6 0.329 Comparative Example 7 0.384

[0097] It can be seen from Table 2 that Examples 1 to 2 use a cross-linked composition of a specific composition and a specific ratio, which improves the tensile strength of the hydrogel and improves the mechanical properties. In Comparative Example 1, the tensile strength is slightly reduced by changing the ratio of ammonium alginate, and in Comparative Example 2, the tensile strength is significantly reduced by changing the ratio of the cross-linked composition, and the mechanical properties are reduced. In Comparative Example 3, ammonium alginate is not added, and the tensile strength is also reduced. In Comparative Example 4, pure polyvinyl alcohol that is not carboxylated is used, and in Comparative Example 5, pure hyaluronic acid that is not thiolated is used. The tensile strength of the hydrogel prepared by the two is greatly reduced. In Comparative Example 6, the addition ratio of methacrylic anhydride in methacrylic anhydride gelatin is changed, and the mechanical properties are reduced. In Comparative Example 7, the viscosity of chitosan is changed, and the tensile strength is also reduced. This shows that all the components in the present invention as a whole technical solution can improve the mechanical properties of the hydrogel.

[0098] (3) High and low temperature cycle test

[0099] The hydrogels prepared in equal amounts in Examples 1 to 2 and Comparative Examples 1 to 7 were stored at low temperature and away from light for 3 days, then stored at high temperature and away from light for 3 days, and then stored at low temperature and away from light for another 3 days. The low temperature treatment and high temperature treatment were cycled 10 times, and the hydrogels were taken out to test their in vitro relaxation efficiency and mechanical properties. The test results are shown in Table 3.

[0100] Table 3 High and low temperature cycle test results

[0101] <![CDATA[In vitro relaxation efficacy / mM -1 s -1 > Tensile strength / MPa Example 1 309 0.505 Example 2 300 0.491 Comparative Example 1 192 0.301 Comparative Example 2 205 0.224 Comparative Example 3 178 0.326 Comparative Example 4 201 0.189 Comparative Example 5 199 0.147 Comparative Example 6 202 0.195 Comparative Example 7 185 0.208

[0102] It can be seen from Table 3 that after 10 low-temperature and high-temperature cycle treatments, the in vitro relaxation efficiency and tensile strength properties of the hydrogels prepared in Examples 1 to 2 did not decrease significantly, while the hydrogels prepared in Comparative Examples 1 to 7 not only decreased in vitro relaxation efficiency but also decreased in tensile strength, indicating that the hydrogels prepared in the present invention can simultaneously ensure that the in vitro relaxation efficiency and mechanical properties are improved, thereby expanding the use conditions of the hydrogels.

[0103] (4) Storage time test

[0104] The hydrogels prepared in equal amounts in Examples 1 to 2 and Comparative Examples 1 to 7 were placed at room temperature in the dark for 3 months, and the hydrogels were taken out after 6 months to test their in vitro relaxation efficiency and mechanical properties. The test results are shown in Table 4.

[0105] Table 4. Test results of storage time

[0106] <![CDATA[In vitro relaxation efficacy / mM -1 s -1 > Tensile strength / MPa Example 1 315 0.510 Example 2 304 0.498 Comparative Example 1 209 0.364 Comparative Example 2 228 0.239 Comparative Example 3 185 0.375 Comparative Example 4 223 0.190 Comparative Example 5 230 0.196 Comparative Example 6 246 0.255 Comparative Example 7 217 0.271

[0107] As can be seen from Table 4, the in vitro relaxation efficiency and mechanical properties of the hydrogel will change with the extension of the storage time, while the hydrogels prepared in Examples 1 to 2 of the present invention almost maintain the original performance parameters, indicating that they have a longer storage time and stability, while the hydrogels of Comparative Examples 1 to 7 have all significantly decreased in various properties after being stored for 3 months, indicating that their stability is poor and they are easily affected by the environment.

[0108] Therefore, the formula components used in the magnetic resonance visualization hydrogel material capable of dynamically monitoring tissue reconstruction of the present invention embed trivalent gadolinium ions into a matrix of sodium alginate and ammonium alginate to form stable nanoparticles or complexes, which not only improves sensitivity and prolongs the imaging window, but also can continuously track the degradation process of the scaffold material, and also improves the mechanical properties and stability of the hydrogel through the cross-linked composition, thereby extending the service life and storage time of the hydrogel.

[0109] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A magnetic resonance visualization hydrogel material capable of dynamically monitoring tissue reconstruction, characterized in that: The magnetic resonance visualization hydrogel material comprises a modified gadolinium contrast agent, a cross-linking composition, methacrylic anhydride gelatin, a cross-linking agent and a photoinitiator.

2. The magnetic resonance visualization hydrogel material capable of dynamically monitoring tissue reconstruction according to claim 1, characterized in that: Magnetic resonance visualization hydrogel materials include the following by mass percentage: Modified gadolinium contrast agents include sodium alginate, ammonium alginate, and trivalent gadolinium ions; The molar ratio of sodium alginate: ammonium alginate: trivalent gadolinium ion is (0.5-0.8): (0.1-0.3):

6.

3. The magnetic resonance visualization hydrogel material capable of dynamically monitoring tissue reconstruction according to claim 2, characterized in that: The preparation method of the modified gadolinium contrast agent is as follows: dissolving sodium alginate and ammonium alginate in water to obtain an alginate aqueous solution; mixing the alginate aqueous solution with an n-pentylamine aqueous solution and stirring evenly; adding hydrochloric acid to the evenly stirred solution to adjust the pH value to 3-5; then dripping an aqueous solution of trivalent gadolinium ions under stirring; adding ethanol after the dripping of the aqueous solution of trivalent gadolinium ions is completed, filtering to obtain a precipitate, and drying the precipitate to obtain a modified gadolinium contrast agent.

4. The magnetic resonance visualization hydrogel material capable of dynamically monitoring tissue reconstruction according to claim 1, characterized in that: The preparation method of methacrylic anhydride gelatin is as follows: gelatin is dissolved in deionized water, and the mixture is stirred to obtain a gelatin solution; methacrylic anhydride is then added dropwise to the gelatin solution; the mixed solution after the addition is dialyzed and freeze-dried to obtain methacrylic anhydride gelatin; The mass volume ratio of gelatin and methacrylic anhydride is 1g:0.1-0.2mL.

5. The magnetic resonance visualization hydrogel material capable of dynamically monitoring tissue reconstruction according to claim 1, characterized in that: The cross-linked composition includes carboxyl-modified polyvinyl alcohol, thiolated hyaluronic acid and chitosan; The mass ratio of carboxyl-modified polyvinyl alcohol: thiolated hyaluronic acid: chitosan is (5-10): (0.5-1): (2-4); The deacetylation degree of chitosan is ≥95%, the viscosity is 100-200 mPa·s, and the molecular weight is 200,000-260,000.

6. The magnetic resonance visualization hydrogel material capable of dynamically monitoring tissue reconstruction according to claim 5, characterized in that: The preparation method of carboxyl-modified polyvinyl alcohol is: Add polyvinyl alcohol into water, completely dissolve at 85-90°C, and cool to room temperature to obtain a polyvinyl alcohol solution; The sodium hydroxide solution and acrylonitrile are mixed evenly, and then added dropwise to the polyvinyl alcohol solution to carry out addition reaction at low temperature. After the reaction is completed, the solution is filtered, and the filtrate is extracted with dichloromethane. The extracted dichloromethane solution is subjected to rotary evaporation to obtain an intermediate product, cyano-modified polyvinyl alcohol; The cyano-modified polyvinyl alcohol is dissolved in methanol, and then added into a mixed solution of sodium hydroxide solution and methanol, and hydrolyzed at 30-50° C., the pH is adjusted to neutral, and deionized water is added dropwise to obtain a gel product, which is washed and dried to obtain the carboxyl-modified polyvinyl alcohol.

7. The magnetic resonance visualization hydrogel material capable of dynamically monitoring tissue reconstruction according to claim 5, characterized in that: The thiolated hyaluronic acid is one of hyaluronic acid-cysteine, hyaluronic acid-cysteamine, hyaluronic acid-cysteine ​​methyl ester, hyaluronic acid-cysteine ​​ethyl ester or a mixture thereof.

8. The magnetic resonance visualization hydrogel material capable of dynamically monitoring tissue reconstruction according to claim 1, characterized in that: The crosslinking agent is one of N,N'-methylene acrylamide, ethylene glycol dimethacrylate, divinylbenzene, hydroxyalkyl methacrylate or a mixture thereof; The photoinitiator is one of 1-hydroxycyclohexyl phenyl ketone, diphenyl (2, 4, 6-trimethylbenzoyl) phosphine oxide, phenyl bis (2, 4, 6-trimethylbenzoyl) phosphine oxide or a mixture thereof.

9. A method for preparing a magnetic resonance visualization hydrogel material capable of dynamically monitoring tissue reconstruction according to any one of claims 1 to 9, characterized in that: The following steps are involved: a) mixing the modified gadolinium contrast agent, the cross-linking composition, and methacrylic anhydride gelatin in water to obtain a mixed solution A; b) adding a cross-linking agent to the mixed solution A under stirring to obtain a mixed solution B; c) adding a photoinitiator to the mixed solution B to obtain a mixed solution C; d) Mixed solution C is subjected to polymerization reaction under ultraviolet light, and after the reaction is completed, a mixture D is obtained; e) The mixture D is centrifuged to obtain a solid, and the obtained solid is washed and dried to obtain a magnetic resonance visualized hydrogel material that can dynamically monitor tissue reconstruction.

10. Use of the magnetic resonance visualized hydrogel material capable of dynamically monitoring tissue reconstruction according to any one of claims 1 to 8 in the preparation of tissue repair materials.

Citation Information

Cited By

  • Magnetic hydrogel, preparation method thereof and non-invasive skin mechanical loading device

    CN119455085A